Perlindungan Hukum bagi Pihak Terkait atau yang Berkepentingan secara Komersial terhadap Desain Industri: Studi Kasus Putusan Pengadilan Negeri Jakarta Pusat Nomor 76/Pdt.Sus-HKI/Desain Industri/2023/PN Niaga Jkt Pst - Joni Harianto; Zeis Zultaqwa; Mohamad Donie Aulia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The Industrial Design Rights of the Koper Generator have been revoked based on the Decision of the Central Jakarta Commercial Court No. 78/Pdt.Sus-HKI/Desain Industri/2023/PN.Niaga,Jkt.Pst. However, even though the registration of the Koper Generator Industrial Design has been revoked, the rights holder continues to exercise his economic rights, thereby causing real losses to the Plaintiff. Therefore, the Plaintiff filed a lawsuit for infringement of industrial design rights and a claim for compensation. The decision on the lawsuit basically rejected the Plaintiff's lawsuit, on the grounds that the Plaintiff did not have legal standing to file a lawsuit for infringement of industrial design rights and a claim for compensation. Based on the results of the study, it was found that legal protection for related parties or parties interested in industrial design rights is only related to filing a lawsuit for cancellation of industrial design rights, but cannot reach legal protection to file a lawsuit for infringement of industrial design rights and a claim for compensation; Legal considerations of the Panel of Judges of the Commercial Court in case No. 76/Pdt.Sus-Hki/Desain Industri/2023/PN.Niaga.Jkt.Pst, is not appropriate, because it does not consider the fact of bad faith from the Defendants who continue to exercise their industrial design rights, even though their industrial design rights (Genset Koper) have been revoked by a court decision. The fact of direct losses suffered by the Plaintiff is not taken into consideration. This can make the judge's decision based on formalistic or procedural justice.